A simple field method for estimating the mass of organic carbon stored in undisturbed wetland soils - Gabriel Magnan; Michelle Garneau; Joannie Beaulne; Martin Lavoie; Stéphanie Pellerin; Léonie Perrier; Pierre J.H. Richard; Nicole Sanderson (Mires and Peat, 2023)
We have compiled a large dataset of peat and soil cores from temperate and boreal regions of eastern Canada to develop a simple field method for estimating the mass of soil organic carbon (SOC) stored in undisturbed wetlands (peatlands, swamps and marshes). We show that it is possible to predict the SOC mass in different wetland types by measuring the organic-rich soil layer thickness in the field. Using this new dataset, we found that SOC mass can be estimated either by using the linear regression equation between peat or soil thickness and SOC mass or by multiplying peat or soil thickness by a mean SOC density. We also show that SOC mass can be estimated by determining the degree of peat humification in the northern peatlands investigated. In this dataset, the precision of estimates is higher for peatlands than mineral wetlands (marshes and swamps), mainly due to the lack of empirical soil core data. The simple approach proposed here could be applied in different wetland regions worldwide where carbon density data from soil cores are available. This cost- and time-efficient method could benefit regional or national-scale carbon inventories.